HYPERTENSIVE PATIENTS ON TREATMENT AND COVID-19 IN FRANCE: FLAHS 2020 SURVEY. (April 2021) - Hanon, Olivier; Pathak, Atul; Silhol, François; Wimart, Marie Catherine; Girerd, Xavier
Abstract : Objective: Evaluate the occurrence of COVID-19 in the first half of 2020 in treated hypertensive patients and describe their medical follow-up during lockdown. Design and method: The FLAHS 2020 survey was performed in July/August 2020 by a self-administered questionnaire sent to 6, 000 individuals aged 35 years and over from Kantar Health's Métascope permanent sampling base (a representative panel of the population living in metropolitan France). A subject was declared ill with COVID if he answered Yes to the question: Have you been ill with COVID-19 with a diagnosis confirmed or not by a doctor? The representativeness of the results for the metropolitan French population was performed by adjusting the data on geographical area, living conditions, socioeconomic category, gender and age. Results: Among the 4069 adults aged 35 years and older, symptomatic COVID-19 was reported by 2.2% [CI95:1.9–2.5] of respondents. The prevalence was 2.7% [CI95:1.4–4.0] among those treated with antihypertensive medication, 2.0% [1.7–2.3] among those not treated, 1.9% [1.3–2.5] among men and 2.5% [1.9–3.1] among women. Among subjects reporting COVID-19. During lockdown, 61.9% of treated hypertensive patients [60.6–63.2] were able to have medical contact, of which 9.8% [8.5–11.1] was by telephone and 5.9% [4.6–7.2] by videoconsultation, which was more frequent in the 35–54 age group with 13.1% [12.5–16.7] than in the 75+ age group with 3.5% [1.2–5.5]. 81.4% [2.8–5.4] of treated hypertensive patients visited the pharmacy at least once, and 4.1% [2.8–5.4] had their treatment delivered at home. Discontinuation of usual treatment was reported by 0.9% [0–2.2] of hypertensive patients, with a higher frequency in those aged 75 years and over (1.7% [0–4.0]). Conclusions: In the first half of 2020 in metropolitan France, COVID-19 in its symptomatic and self-reported form concerned treated hypertensive patients and the general population in a similar way. During lockdown there was no obvious disruption of care in the treated hypertensive patients and teleconsultation had a significant development, particularly for the visio-consultation in the 35–54 age group.